Black teeth: beauty or caries prevention? Practice and beliefs of the Kammu people - Tayanin GL, Bratthall D. (Blackwell Synergy, 2006)
To be beautiful and caries-free, Kammu women in Laos and Vietnam habitually paint their teeth black.